Training on Making Organic Fertilizer at SMPN 5 Satu Atap Labuhan Badas, Sumbawa Regency - Khairi, Alfassabiq; Dwilaksono, Fahmi; Purnamasari, Ayu; Ardiansah, Gatot (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Organic fertilizer application is a fundamental approach to improving soil structure and nutrient content in order to encourage sustainable agricultural development and high economic benefits. Promoting the use of organic fertilizers for the young generation is one of the steps to educate them on how to utilize organic manure. The community service activity aimed to provide information and an introduction to plants through the use of school grounds for cultivation and to introduce the making of organic fertilizers at the junior high school level. The organic fertilizer was produced from decomposing organic materials such as dry leaves, cow manure, brown sugar, and bioactivator. The community service program presented a positive experience for students by gaining knowledge and experience in making organic fertilizer. They produced organic fertilizer that met the required parameters and was successfully applied to the schoolyard's plants. As a result, they can recognize the health benefits associated with the use of organic fertilizers.